How Computer Literacy and Socioeconomic Status Affect Attitudes Toward a Web-Based Cohort: Results From the NutriNet-Santé Study - Pouchieu, Camille; Méjean, Caroline; Andreeva, Valentina A; Kesse-Guyot, Emmanuelle; Fassier, Philippine; Galan, Pilar; Hercberg, Serge; Touvier, Mathilde (Journal of Medical Internet Research, 2015)
BackgroundIn spite of the growing literature in the field of e-epidemiology, clear evidence about computer literacy or attitudes toward respondent burden among e-cohort participants is largely lacking. ObjectiveWe assessed the computer and Internet skills of participants in the NutriNet-Santé Web-based cohort. We then explored attitudes toward the study demands/respondent burden according to levels of computer literacy and sociodemographic status. MethodsSelf-reported data from 43,028 e-cohort participants were collected in 2013 via a Web-based questionnaire. We employed unconditional logistic and linear regression analyses. ResultsApproximately one-quarter of participants (23.79%, 10,235/43,028) reported being inexperienced in terms of computer use. Regarding attitudes toward participant burden, women tended to be more favorable (eg, “The overall website use is easy”) than were men (OR 0.65, 95% CI 0.59-0.71, P<.001), whereas better educated participants (>12 years of schooling) were less likely to accept the demands associated with participation (eg, “I receive questionnaires too often”) compared to their less educated counterparts (OR 1.62, 95% CI 1.48-1.76, P<.001). ConclusionsA substantial proportion of participants had low computer/Internet skills, suggesting that this does not represent a barrier to participation in Web-based cohorts. Our study also suggests that several subgroups of participants with lower computer skills (eg, women or those with lower educational level) might more readily accept the demands associated with participation in the Web cohort. These findings can help guide future Web-based research strategies.